Assessment Scales for Patients with Advanced Huntington's Disease: Comparison of the UHDRS and UHDRS‐FAP. Issue 5 (24th August 2018) - Winder, Jessica Y.; Achterberg, Wilco P.; Marinus, Johan; Gardiner, Sarah L.; Roos, Raymund A.C.
Abstract: Background: The standard clinical assessment tool in Huntington's disease is the Unified Huntington's Disease Rating Scale (UHDRS). In patients with advanced Huntington's disease ceiling and floor effects of the UHDRS hamper the detection of changes. Therefore, the UHDRS‐For Advanced Patients (UHDRS‐FAP) has been designed for patients with late‐stage Huntington's disease. Objectives: This cross‐sectional study aims to examine if the UHDRS‐FAP can differentiate better between patients with advanced Huntington's disease than the UHDRS. Methods: Forty patients, who were institutionalized or received day‐care, were assessed with the UHDRS, UHDRS‐FAP, and Care Dependency Scale (CDS). The severity of Huntington's disease was defined by the Total Functional Capacity (TFC). Comparisons between consecutive TFC stages were performed for all domains of the UHDRS, UHDRS‐FAP, and CDS using Mann‐Whitney U tests. Results: The motor scores of the UHDRS‐FAP and UHDRS were the only subscales with significantly worse scores in TFC stage 5 compared to stage 4. In TFC stages 4‐5, the range of the UHDRS‐FAP motor score was broader, the standard error of measurement was lower, and the effect size r was higher than for the UHDRS motor score. The CDS declined significantly across all TFC stages. Conclusions: Our results suggest that the UHDRS‐FAP motor score might differentiate better between patients with severe Huntington's disease than the UHDRS motor score. Therefore, the UHDRS‐FAP motor score is potentially a better instrument than the UHDRS motor score to improve disease monitoring and, subsequently, care in patients with advanced Huntington's disease in long‐term care facilities.